Wajah Hukum “Bermuka Dua” dalam Regulasi Usia Perkawinan di Indonesia - Sugitanata, Arif; Bustomi, Ahmad; Aminah, Siti (Institut Agama Islam Negeri Metro, 2024)
The legal age of marriage in Indonesia has become a compelling issue and has been extensively studied by scholars. Although the national law stipulates that the legal age of marriage must be 19 years for both males and females, inpractice, some loopholes can be exploited, specifically through marriage dispensation. This article aims to elucidate the disparity between